The neurofeedback course using of high skilled gymnasts at competitive period - Strizhkova, O.; Cherapkina, L.; Strizhkova, T. (Journal of Human Sport & Exercise, 2014)
The research was carried out with 28 high skilled gymnasts (15 - main group, 13 - control group) allowed to define the neurofeedback influence on the functional condition of sportswomen in competitive period. The neurofeedback course promotes improvement of rapidity of complex coordinating motions learning, vestibular stability and self-estimation of functional condition. Also it conducts the alpha-rhythm power increasing at left hemisphere. The neurofeedback course efficiency is defined by index of change of course average alpha-rhythm power with 100% prognostic accuracy. The attention switching, attention stability and self-estimation of sleep and memory are predictors of neurofeedback course successfulness.